Literacies - Kalantzis, Mary.; Cope, Bill. (Cambridge, UK. : Cambridge University Press, 2012)
Provides a comprehensive introduction to literacy pedagogy within today's new media environment, focusing not only on reading and writing, but also on other modes of communication, including oral, visual, audio, gestural and spatial. This focus is designed to supplement, not replace, the role of alphabetical literacy.
Includes bibliographical references (p. 421-447) and index.
Keywords: Literacy programs; Literacy -- Social aspects; Sociolinguistics; Mass media and language